Glyphosate improves long-term control of smooth scouringrush (Equisetum laevigatum) with chlorsulfuron + metsulfuron - Drew J. Lyon; Mark E. Thorne (Weed Technology)
Smooth scouringrush is an herbaceous perennial with an extensive underground rhizome system that has invaded no-till dryland production fields in the inland Pacific Northwest. The objective of this field study was to determine whether there were any short- or long-term benefits to tank-mixing chlorsulfuron + metsulfuron with glyphosate for smooth scouringrush control. Field studies were conducted at three sites across eastern Washington from 2020 to 2024. Glyphosate was applied during fallow periods at 0, 1,260, 2,520, and 3,780 g ae ha−1 with and without chlorsulfuron + metsulfuron applied at 21.9 + 4.4 g ai ha−1. Smooth scouringrush stem density was evaluated 1, 2, and 3 yr after treatment. Chlorsulfuron + metsulfuron provided excellent control of smooth scouringrush (<5 plants m−2) for the first 2 yr at all three sites, and there was no observed benefit of tank-mixing with glyphosate. This continued to be the case 3 yr after treatment at two of the sites, but at one site, adding glyphosate at 2,520 or 3,780 g ha−1 to chlorsulfuron + metsulfuron decreased stem density compared to chlorsulfuron + metsulfuron applied alone. For treatments containing glyphosate only, the greatest efficacy 3 yr after treatment was achieved at the highest application rate of 3,780 g ha−1. Although no short-term benefit was observed in adding glyphosate to chlorsulfuron + metsulfuron for smooth scouringrush control, at one of three sites the duration of control was increased by at least 1 yr with the addition of glyphosate at a rate of 2,520 g ha−1 or more and an organosilicone surfactant as tank-mix partners.